(untitled) (The International Journal of Educational Sciences and Arts, 2025)
The study aimed to identify the most important professional needs of school counselors in Hail schools from their own perspectives, as well as to explore the challenges that hinder meeting these professional needs, and to examine the proposals offered by counselors to fulfill these needs. The research adopted a descriptive methodology and utilized a questionnaire to collect data from a sample of 115 male and female school counselors in Hail schools. The results indicated that the overall level of agreement regarding the dimension of professional needs of school counselors in Hail was "high," with a mean score of (3.618) and a standard deviation of (0.696). Similarly, the dimension of challenges hindering the fulfillment of professional needs received a "high" level of agreement, with a mean score of (3.682) and a standard deviation of (0.659). Furthermore, the dimension of proposals offered by school counselors to meet their professional needs also received a "high" level of agreement, with a mean score of (3.767) and a standard deviation of (0.631). The study recommended the development of specialized professional training programs tailored to the needs expressed by school counselors, taking into account specific areas such as psychological, behavioral, and academic counseling. It also emphasized the importance of creating a supportive and motivating work environment for counselors, including reducing non-guidance-related administrative burdens and providing the necessary resources to perform their tasks effectively.